Optimalisasi Penggunaan Zakat Untuk Memutus Rantai Kemiskinan di Desa Laud Dendang Kecamatan Percut Sei Tuan - Lubis, Nurul Rafiqoh; Nasution, Yenni Samri Juliati (Universitas Labuhanbatu, 2023)
This study aims to examine the management of zakat and the empowerment of the poor in an effort to alleviate poverty in the village of Laud Dendang, Deli Serdang.Data collection methods are conducted through field studies, interviews, and data analysis.The results showed that the management of zakat by the Badan Amil Zakat Nasional (BAZNAS) has had a positive impact in empowering the poor.Zakat funds collected and managed properly are used for the program